2017
DOI: 10.1016/j.jcma.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prognostic factors and implication of lymph node dissection in intrahepatic cholangiocarcinoma: 10-year experience at a tertiary referral center

Abstract: Regional lymph node metastasis, positive resection margin, periductal infiltration, and poor differentiation were poor prognostic factors in patients with ICC after curative surgery. Lymph node dissection did not show survival benefits, but was useful for nodal staging. However, lymph node metastases were strongly associated with late T stages, multiple tumors, and elevated serum CEA and CA19-9 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Most of cLNM-negative patients (80%) showed consistent diagnosis after final pathologic evaluations. And we found cLNM-negative ICC patients showed almost the same survival rate when compared with pLNM-negative ICC patients, this result similar with literature report [ 21 , 22 ]. Besides, with the development of imaging system, the accuracy of LNM detection by preoperative imaging examination has been improving in recent years [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Most of cLNM-negative patients (80%) showed consistent diagnosis after final pathologic evaluations. And we found cLNM-negative ICC patients showed almost the same survival rate when compared with pLNM-negative ICC patients, this result similar with literature report [ 21 , 22 ]. Besides, with the development of imaging system, the accuracy of LNM detection by preoperative imaging examination has been improving in recent years [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, independent factors associated with decrease DFS were tumor size > 5 cm, periductal infiltrating growth type tumor, multiple tumor, vascular invasion, and lymph node metastasis. These factors, however, had been demonstrated as important determinant of OS and DFS in different studies [5,6,17,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been also demonstrated that liver-specific deletion of PTEN in a mouse model results in the development of ICC (26,27). As an important tumor suppressor, PTEN mainly acts to dephosphorylate phosphatidylinositol-3,4,5-trisphosphate [PtdIns (3,4,5) P3], which potently activates 3-phosphoinositide-dependent kinase (PDK) and protein kinase B (AKT) (28). However, PTEN loss leads to excessive recruitment of PtdIns (3,4,5)P3 at the plasma membrane, thereby activating a subset of proteins, including the AKT family and PDK1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…As an important tumor suppressor, PTEN mainly acts to dephosphorylate phosphatidylinositol-3,4,5-trisphosphate [PtdIns (3,4,5) P3], which potently activates 3-phosphoinositide-dependent kinase (PDK) and protein kinase B (AKT) (28). However, PTEN loss leads to excessive recruitment of PtdIns (3,4,5)P3 at the plasma membrane, thereby activating a subset of proteins, including the AKT family and PDK1 (28). AKT signaling induces cell survival, cell proliferation, angiogenesis and cellular metabolism via phosphorylating downstream signaling proteins (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation